Formulation, implementation, and control of competitive strategy - Pearce, John A.; Robinson, Richard B. (Boston : Irwin/McGraw-Hill, 2000)
Business
2002-06-05
Keywords: Stretegic planning; Strategic planning case studies; Strategic management